Islam in Front of the Challenges of Modernity: World Politics, State System, Public Opinion - V. V. Orlov (Vestnik MGIMO-Universiteta)
Review of the textbooks: Islam in World Politics in Early XXIth Century: A Textbook / L.M. Yefimova, M.A. Sapronova, eds.; [A.M. Ahunov, V.A. Ahmadullin, R.I. Bekkin a. o.]; Moscow State Institute of International Relations (University) of Ministry of Foreign Affairs, Russian Federation, Dept. of Oriental Studies. Moscow: MGIMO–University, 2016. 345, [1] p. (In Russ.);Islam in the State and Socio-Political Systems of the Eastern Countries: A Textbook / L.M. Yefimova, M.A. Sapronova, eds.; [K.P. Borishpolets, R.D. Daurov, B.V. Dolgov a. o.]; Moscow State Institute of International Relations (University) of Ministry of Foreign Affairs, Russian Federation, Dept. of Oriental Studies. Moscow: MGIMO–University, 2018. 350, [1] p. (In Russ.);Muslim Socio-Political Ideas in Front of the Challenges of Modernity: A Textbook / L.M. Yefimova, M.A. Sapronova, eds.; [B.V. Dolgov, S.B. Druzhilovsky, L.M. Yefimova a. o.]; Moscow State Institute of International Relations (University) of Ministry of Foreign Affairs, Russian Federation, Dept. of Oriental Studies. Moscow: MGIMO–University, 2018. 192, [2] p. (In Russ.).The set of textbooks, written by the lecturers of Department of Oriental Studies, MGIMO–University, is a very useful publication both in terms of research and education. It covers the wide field of key problems of contemporary Islam and fills out some gaps in Russian studies of Islam.The first book of the series is focused on processes of globalization and democratization in Islamic world. The authors examine the role of Muslim states in multi-vector development of regional and global politics, analyze the impact of Islamic structures and concepts on present system of international relations. In the second book the authors emphasize the role of Islamic factor in domestic political life of specific countries and regions of the Muslim world. The authors focus on fundamental issues of constitutional law, functioning of supreme state bodies, building of parties and political systems. In the third book of the series the authors review the ideas of contemporary Muslim philosophers, public figures, political writers – both of conservative-fundamentalist and liberal-modernist orientation, basing on numerous facts. The authors managed to present the diversity of solutions, proposed by Muslim politicians and thinkers aimed at facing a number of challenges such as modernization and globalization, migration crises, poor ecological conditions, rise of social inequality, erosion and substitution of traditional values of Islam, etc.The textbooks in review may be of special interest not only for teachers and students at universities and high schools, but also for specialists in Oriental studies, political studies, as well as for broad audience of readers.